Segmentation of Residential Customer Load Profile in Peninsular Malaysia using Jenks Natural Breaks - Khamis N.; Sin T.C.; Hock G.C. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric power measurement; Image segmentation; Random processes; Sales; Load profiles; Off-Peak; Peak; Residential customers; Time duration; Time of use; Housing